Water demand management in Mediterranean regions - Giulio Querini; Salvo Creaco (European Regional Science Association (ERSA), 2005)
Water sustainability needs a balance between demand and availability: 1) Water demand management: demand may be managed by suppliers and regulations responsible persons, using measures like invoicing, consumptions measurement and users education in water conservation measures; 2) Augmentation of water supply: availibility may be augmented by infrastructural measures, waste water reuse, non-conventional resources and losses reduction. Water Demand Management is about achieving a reduction in the use of water resources, normally through increased efficiency of water application. The main objective of this paper is the application of these concepts to Mediterranean regions.
Keywords: 330